THE POSITIVE IMPACT OF BEING A NARCISSTIC PORTRAYED BY THE MAIN CHARACTER IN NETFLIX SERIES “LUCIFER” - Islami, Balqis Syaidina; Weda, Sukardi; Sunra, La (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
Abstract Lucifer - a serial film about a former hell keeper with a nearly perfect physique for a human who decides to come down to earth and chooses Los Angeles as his destination. The story begins with Lucifer meeting a beautiful pop star he knows, who is found brutally murdered outside his nightclub. For the first time in history after centuries he was created, something inside him awakened, a strange feeling, after witnessing this murder scene Lucifer felt confused and didn't know whether it was a normal feeling or a Sympathy that was impossible for a demon with a narcissistic Personality disorder. In general, people describe the word narcissism as something that is definitely bad, especially when it is associated with the word personality disorder, but this article will discuss the opposite. The main objective of this study is to recount the benefits or positive things contained in the narcissistic nature of a Lucifer Morningstar depicted in the Netflix original series, Lucifer. That being a person with Narcissistic Personality Disorder (NPD) is not always negative. The authors used the research method of library research methods with textual analysis as the method of analysis. To prove the motion regarding narcissistic personality disorder in the main character in the Lucifer movie series, the authors analyze two main aspects, namely intrinsic and extrinsic aspects. The intrinsic aspects that will be analyzed are the narrative elements shown through characterizations, as well as uncovering Lucifer's personality disorder and the cause of the disorder itself. The results of this study prove that the positive and beneficial impact on Lucifer's daily life as a person with NPD is proven from several aspects in the form of; Lower anxiety, take better care of his self, easier to get a job, and build stronger relationship. Keywords: Lucifer, Positive, Narcissism Personality Disorder, Character